A STUDY ON LORD JIM'S ANXIETY IN JOSEPH CONRAD'S LORD JIM: A PSYCHOANALYTIC APPROACH - KURNIAWATI, GESANG ARI (2007)
The major problem of this study is how anxiety is reflected in the major character's personality. The aim of this study is to analyze Joseph Conrad's Lord Jim based on the structural elements and the personality of the major character based on Psychoanalytic Approach. This study focuses on the major character, namely Lord Jim. The benefit of this study is to give additional information which can be used by the other literature researchers who are interested in analyzing this play. This study uses two data sources, namely primary and secondary data source. The primary data source is the novel itself, while the secondary data are taken from some information needed. The method of data collection is qualitative method. Based on the analysis, the outcome of this study shows that the problem of major character encounters causes the conflict of his mental condition. Then, it develops to become anxiety and influences him to do some ways to escape from it. Then his ways are not effective to overcome the problem because finally he died.